AF in Cancer Patients: A Different Need for Anticoagulation? - Ana Pardo Sanz; José Luis Zamorano Gómez (European Cardiology Review)
Cancer and cancer therapies might be a risk factor for developing Atrial Fibrillation (AF). It remains unclear if one is the cause or consequence of the other, or if they simply coexist. An unpredictable response to anticoagulation can be expected, as a result of the lack of information in oncology patients. The balance between thromboembolic and bleeding risks of AF in these patients is particularly challenging. Little is known about whether embolic and bleeding risk scores used for the general population can be applied in oncologic patients. Cardiology involvement in the management of these patients seems to be associated with favourable AF-related outcomes.